The Applicability of Scientific Approach to Increase the Student’s Critical Thinking Skill in Mathematic of the Student 5 Grade - Lestari, Tri; Mawardi, Mawardi; Wardani, Krisma Widi (MODELING: Jurnal Program Studi PGMI, 2019)
The goal of this research is to increase the student’s critical thinking skill using scientific approach in mathematic of the students 5 grade SD Negeri Ledok 01 Salatiga. It use Classroom Action Research (CAR), it will do to solve learning problems in the classroom. The writer does Classroom Action Research (CAR) collaboratively with the teacher of 5 grade SD Negeri Ledok 01 Salatiga. The subjects of this research is the students 5 grade SD Negeri Ledok 01 there are 30 students consists of 16 boys and 14 girls. The result of the analysis data show the students critical thinking skill of the pre-cycle is 26% high level, 20% intermediate level and 54% in the low level. First cycle it about 50% high level, 43% intermediate level, and 7% low level, second cycle 57% high level and 43% intermediate. Based on the result above, the writer can conclude the scientific approach is increasing the students critical thinking skill in mathematic of the student 5 grade SD Negeri Ledok 01 Salatiga.